Gongola Basin Geoid Determination using Isostatic Models and Seismic Reflection Data and Geophysical Interpretation - E.E. Epuh; J.B. Olaleye; O.G. Omogunloye (Геофизический журнал, 2016)
The application of Stokes’ formula to create geoid undulation requires no masses outside the geoid. Usually, a constant density of 2.67g / cm3 is used in the determination of the geoid which introduces error in the reduced gravity anomalies (Helmert’s condensation) and consequently the geoid. In this paper, isostatic models of Airy-Heiskanen and Pratt-Hayford were utilized in the determination of the geoid by considering the planar and spherical approximation models. The indirect effect of the topographic lateral density variation on the geoid was computed as additive correction for the improvement of the accuracy of the computed geoid. Additional density information deduced from seismic and well log data was considered for the variable density computation. The geopotential geoid undulations were computed from the EGM 2008 model. The residual geoid was obtained by subtracting the local isostatic geoid from the geopential geoid. Geoid and gravity admittance studies were also carried out to complement the results from the residual geoid. The planar and spherical approximation results showed similar characteristics; but a change in magnitude in both models. Our results suggest that the effects of topographic lateral density variations in geoid determination are significant and should be considered in rift basins. The geophysical analysis of the geoid results show that the north-east domain has positive residual geoid which indicates the presence of high density intrusive igneous rocks, while the south-east has negative residual geoid which indicates the dominant presence of low density sedimentary rocks. The results also show that the radial distribution of the anomalous mass obtained using the geoid/residual geoid anomaly uniquely matched that obtained using the seismic reflection data which inferred the presence of hydrocarbon accumulation in the south east zone of the project area. The gravity and geoid admittance studies corroborated the residual geoid and seismic reflection results